THE RISK FACTORS AND EVALUATION CRITERIA FOR PROGRESSION OF ATHEROSCLEROSIS IN ONE YEAR POST CORONARY BYPASS - A. V. Bezdenezhnykh; A. N. Sumin; Ya. V. Kazachek; A. V. Osokina; N. V. Kondrikova; Yu. V. Bayrakova; S. V. Ivanov; O. L Barbarash (Российский кардиологический журнал)
Aim. To assess risk factors and to compare evaluation criteria of non-coronary atherosclerosis progression in coronary heart disease patients in 1 year post coronary bypass surgery (CBG).Material and methods. Of 732 consequtive patients (586 males, 146 females, median age 59 y.o.) underwent CBG, 504 were investigated second time in 1 year after operation. Patients underwent ultrasound study (US) of carotid and peripheral arteries with measurement of intima-media thickness. Ankle-brachial index (ABI) was measured automatically with sphygmomanometer VaSeraVS-1000 (Fukuda Denshi,Japan). In blood, lipids were tested. Based on the stenosis indexes NASCET and ECST, the groups were selected: <30% (minor stenosis); 30-49% (moderate stenosis); 50-69% (severe stenosis); 70-99% (critical stenosis); occlusion; absence of stenoses. Criteria for progression of atherosclerosis was existence of at least one sign: transition of non-coronary stenosis from one group to another by US; decrease of ABI during 1 year below0,9 in normal baseline;  decrease of ABI >10% if the baseline ABI lower than 0,9. For analysis, two groups were selected: group 1 (n=375) without progression, and group 2 (n=129) with progression of atherosclerosis. The relation of possible factors to probaility of  on-coronary atherosclerosis progression was evaluated in logistic regression model.Results. Levels of the total cholesterol (TC) and low density lipoproteides cholesterol (LDL-C) were higher in patients with progression of atherosclerosis. In dynamics, significantly in both groups the level of high density lipoproteides cholestrol (HDL-C) increased (p<0,001), and triglycerides decreased (p<0,05). In intergroup analysis, ABI values were higher in the group with no progression of atherosclerosis (p<0,001). In dynamics, in the group of atherosclerosis progression there was significant ABI decrease (p<0,05). In non-progression group ABI, remaning in reference range, significantly decreased during a year after CBG (p<0,05). Thickness of CIM in the non-progression group significantly decreased during a year post-surgery, but in progression group the difference was non-significant. In monofactorial logistic regression, probability of atherosclerosis progression increased with the increase of age, in smoking anamnesis before surgery, in increase of TC and LDL-C, as with GFR decline and in baseline multifocal atherosclerosis presence. Multifactorial analysis showed remaining statistical significance for the several arterial regions, and adverse lipid profile.Conclusion. In one year post-CBG, progression of non-coronary atheroslerosis is marked in 25,6% of patients. In one year post-CBG, ABI decreases independently from the presence of non-coronary atherosclerosis. Factors associated with atherosclerosis progression, were multifocality, level of TC and LDL-C.